Successful Use of Extracorporeal Life Support after Double Traumatic Tracheobronchial Injury in a Patient with Severe Acute Asthma - Valette, Xavier; Desjouis, Aurélie; Massetti, Massimo; Hanouz, Jean-Luc; Icard, Philippe (Pulmonary Medicine, 2011)
We report the case of an asthmatic patient with blunt trachea and left main bronchus injuries who developed acute severe asthma after surgical repair. Despite medical treatment and ventilatory support, asthma persisted with high airway pressures and severe respiratory acidosis. We proposed venovenous extracorporeal life support for CO2 removal which allowed arterial blood gas normalization and airway pressures decrease. Extracorporeal life support was removed on day five after medical treatment of acute severe asthma. So we report the successful use of extracorporeal life support for operated double blunt tracheobronchial injury with acute severe asthma.